2022
DOI: 10.1111/dmcn.15186
|View full text |Cite
|
Sign up to set email alerts
|

Best evidence for improving function in children with cerebral palsy: Success is within reach

Abstract: This letter to the editor is on the Clinical Practice Guide by Jackman et al. on pages 536–549 of this issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…The comprehensiveness of the NTT treatment can be an important reason explaining the presented effect. This is in line with the evidence on dose-intensive studies, as reported in the field of children with Cerebral Palsy [ 35 ] and children with motor deficits [ 36 ], showing that increased dosage of intervention is showing higher effects compared to low dosage intervention.…”
Section: Discussionsupporting
confidence: 89%
“…The comprehensiveness of the NTT treatment can be an important reason explaining the presented effect. This is in line with the evidence on dose-intensive studies, as reported in the field of children with Cerebral Palsy [ 35 ] and children with motor deficits [ 36 ], showing that increased dosage of intervention is showing higher effects compared to low dosage intervention.…”
Section: Discussionsupporting
confidence: 89%
“…2 Unfortunately, there are limitations in complex disability research, which has been found to lack rigour and thus the certainty to provide evidence-based intervention at all stages of life. [8][9][10] These limitations can be countered using good clinical reasoning, like the structured BCRF clinical reasoning cycle. This agrees with the suggestion that 'clinical reasoning and decision-making should always involve weighing up individual children and young people's and families' preferences, context, clinical and health system affordances, plus the certainty of the evidence'.…”
Section: E T T E R T O T H E E D I T O Rmentioning
confidence: 99%
“…7 While the letter from Damiano and Novak questions the absence of rigour in the BCRF, those published guidelines included only 4/13 good practice recommendations based on graded evidence while the remainder seemed to be based on the authors' opinion of what they considered best, which they acknowledged as being different from evidence-based recommendation. 7,9 There are also limitations to systematic reviews and metaanalyses, 9 although these are designed to look rigorously for consistency in treatment effects across a number of similar studies. This was not the case in the meta-analysis by Te Velde et al, as subject groups were mixed, dosage was not necessarily equal, some studies focused on upper limb and others on the lower limb.…”
Section: E T T E R T O T H E E D I T O Rmentioning
confidence: 99%